Hippocampal Dentate Gyrus Atrophy Predicts Pattern Separation Impairment in Patients with LGI1 Encephalitis. (21st February 2019) - Hanert, Annika; Rave, Julius; Granert, Oliver; Ziegler, Martin; Pedersen, Anya; Born, Jan; Finke, Carsten; Bartsch, Thorsten
Highlights: Patients with LGI1 encephalitis show a hippocampal affection with memory deficits. LGI1 patients were impaired in hippocampal pattern separation performance. Volume of dentate gyrus best predicted deficits in pattern separation performance. Deficits in recognition memory were strongest predicted by hippocampal CA1 volume. Clinical MRI show hippocampal sclerosis focused on the dentate gyrus. Abstract: Day-to-day life involves the perception of events that resemble one another. For the sufficient encoding and correct retrieval of similar information, the hippocampus provides two essential cognitive processes. Pattern separation refers to the differentiation of similar input information, whereas pattern completion reactivates memory representations based on noisy or degraded stimuli. It has been shown that pattern separation specifically relies on the hippocampal dentate gyrus (DG), whereas pattern completion is performed within CA3 networks. Lesions to these hippocampal networks emerging in the course of neurological disorders may thus affect both processes. In anti-leucine-rich, glioma-inactivated 1 (LGI1) encephalitis it has been shown in animal models and human imaging studies that hippocampal DG and CA3 are preferentially involved in the pathophysiology process. Thus, in order to elucidate the structure–function relationship and contribution of hippocampal subfields to pattern separation, we examined patients ( n  = 15, age range: 36–77 years) with the rare LGI1 encephalitis showing lesions to hippocampal subfields. Patients were tested 3.53 ± 0.65 years after the acute phase of the disease. Structural sequelae were determined by hippocampal subfield volumetry for the DG, CA1, and CA2/3. Patients showed an overall memory deficit including a significant reduction in pattern separation performance ( p  = 0.016). In volumetry, we found a global hippocampal volume reduction. The deficits in pattern separation performance were best predicted by the DG ( p  = 0.029), whereas CA1 was highly predictive of recognition memory deficits ( p  < 0.001). These results corroborate the framework of a regional specialization of hippocampal functions involved in cognitive processing.